Adenomyosis in magnetic resonance imaging – the value of SE T2 sequence using body arrey - Majos, Agata; Bakalarz, Marek; Stachowiak, Grzegorz; Stefańczyk, Ludomir; Jędrzejczyk, Sławomir (Menopause Review/Przegląd Menopauzalny, 2005)
Adenomyosis is an non-neoplastic invasion of the ectopic endometrium into the myometrium. Clinical symptoms are not characteristic and do not allow to establish the correct diagnosis. Diagnostic imaging plays the crucial role in that field. The most widely used endovaginal sonography (ES) reveals some limitations. Magnetic resonance (MR) imaging can be a supplementary technique. The aim of the study was to determine the value of SE T2 sequence in diagnosis of adenomyosis by using the conventional, built into the MR scanner, body arrey. 12 women underwent the MRI examination. Sonography and following treatment confirmed the uterine adenomyosis . The high agreement between ES and MRI was proved. SE T2 sequence with use of the conventional body arrey is realiable in adenomyosis evaluation. The proposed protocol decreases costs of MRI examination and extends availability of the procedure.